Respuesta :

Answer:

2i√3

Step-by-step explanation: Simplify the radical by breaking the radicand up into a product of known factors.

Hope this helps! :) ~Zane

For this case we must find an expression equivalent to:

[tex]\sqrt {-12}[/tex]

Then, rewriting:

[tex]\sqrt {-1 (12)} =\\\sqrt {-1} * \sqrt {12} =[/tex]

We know that:

[tex]i = \sqrt {-1}\\12 = 4 * 3 = 2 ^ 2 * 3[/tex]

Then we have:

[tex]i * \sqrt {2 ^ 2 * 3} =\\i * 2 \sqrt {3} =[/tex]

Finally we have:

[tex]2i \sqrt {3}[/tex]

Answer:[tex]2i \sqrt {3}[/tex]